(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
ABSTRACT Society, like everything that arises from human beings, is cyclical. you already saw. Therefore, the main objective of this excerpt was to investigate the Brazilian democratic system. As an accessory, democracy and its applicability were conceptualized after the 1988 Constitution. State authority versus popular will was deliberated. The phenomenon of disbelief in the Brazilian electoral system was exposed through the massive distribution of fake news. The argument referred to the invocation of article 142 of the Federal Constitution for reasons of public order. Suggestions were presented for the direct viability of democracy in Brazil and it was concluded that democracy is the pillar of fundamental rights and guarantees and, despite needing constant improvement, is capable of structuring and organizing the development of the democratic rule of law. It was concluded that democracy is under constant attack on a daily basis; Under control, acts like fake news and popular disinterest can be detrimental to democracy in the long term; However, the democratic system remains the closest to equality and justice, whether in the legal, political, economic or social sphere. To carry out the study, in terms of the method, qualitative-quantitative research is used, based on the search and analysis of writings on the topic; in fact, the hypothetical-deductive method is used to reach satisfactory conclusions consistent with the proposed topic. Keywords: Democracy; Popular sovereignty; Government Regime; Fake News.